KORELASI TINGKAT ADOPSI MEDIA INTERNET TERHADAP KEBERHASILAN STUDI MAHASISWA JURUSAN SOSIOLOGI UNIVERSITAS RIAU - Raudhatul Jannah; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aimed at knowing the correlation of the level of the adoption of internet media towards the study success of Sociology Department Students of Universitas Riau.The research design of this study was quantitative study using correlation formula of Pearson Product Moment and using probability approach withsimple random sampling technique. The data collection technique used were questionnaire sheets and direct observation. The dataanalysistechnique used was quantitative analysis, provided with form of table with attached explanations. The result of this research was there was a significant correlation between the level of the adoption of internet media towards the study success of Sociology Department Students of Universitas Riau. Based on the result of this study, it is suggested to the students to be able to utilize the internet as carefully and wisely as possible in order to enhance the study success of Sociology Department Students of Universitas Riau.Keywords :Adoption, Internet, Success, Study.